Implementation Of Dual-Use Technologies in Defense and Public Security - Kristijan Ilovača (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This paper presents a comprehensive analysis of the mechanisms for introducing dual-use technologies into defense and public-security frameworks. The topic’s relevance stems from rapid advances in technical solutions that blur the traditional lines between civilian and military applications—creating new opportunities to boost efficiency across multiple sectors, while simultaneously posing significant risks of international destabilization and threats to national integrity. The study aims to survey contemporary models for integrating dual-use technologies, to identify regulatory, economic, and ethical constraints, and to pinpoint the most promising practices for strengthening defense capabilities and enhancing public protection in a holistic manner. Emphasis is placed on technological domains such as artificial intelligence, biological systems, cybersecurity, and autonomous unmanned platforms. Drawing on current research, the paper demonstrates how adaptive management strategies for dual-use technologies can deliver flexible responses to rapidly evolving challenges. Special attention is given to the need for robust interagency and transnational coalitions, as well as the creation of legal frameworks that simultaneously foster innovation. The findings will benefit defense-policy and security-management professionals, technology-transfer experts, and representatives of governmental bodies and high-tech firms seeking balanced solutions in an era of technological turbulence.